If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 2x + x + -1 Multiply f * x fx = 2x + x + -1 Reorder the terms: fx = -1 + 2x + x Combine like terms: 2x + x = 3x fx = -1 + 3x Solving fx = -1 + 3x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -1x-1 + 3 Simplifying f = -1x-1 + 3 Reorder the terms: f = 3 + -1x-1
| 3n-13=n+6 | | (x+5)(x-5)(x-7)=0 | | x^2+8x-7=8 | | 16x+18y+10x-7y= | | 5y^2+8y= | | 3k-2=39 | | 5X^3/(10x^2+5x) | | 5=-5+2x | | -x+3x-9=5 | | 9x+6-8=-38 | | 4x-3+2x+5=20 | | 15/2=5w | | 5x^3/10x^2+5x | | 5.00+0.8x=14.6 | | 5+8x=14.6 | | 3(10+-2y)+4y=8 | | 3-(4b-2)=3-4b-2 | | -4x-3=-6x-9 | | (8-x)+4=0 | | 5x+646464646464644646464646464644664464646464645554987604596=3 | | m^2-8m+16/5m^2+m | | 10+3x=2x-8x+40 | | y=-0.25x | | -12=39-6 | | x+2-9102301+78xypn-9087px=-12123 | | y=-0.25 | | 4a+1.5=13.5 | | -1=3(x-4) | | 2(x+1)-3(9-x)=-5 | | (4-3x)/2=5 | | 5/9-4/9 | | 900x-v+73r-px-2-p=529 |